Exploring faith-based interventions for mental health and suicide in Malaysia: An Islamic perspective - Roslan, Mohammad Nasrul Hakim; Hussain, Muhammad Hafis; Malkan , Siti Norma Aisyah; Jaafar , Abu Bakar; Asmadi, Athira Ayuni; Ayub, Mohd Nasir (Journal of Islamic, Social, Economics and Development, 2025)
Mental health encompasses an individual's emotional, psychological, and social well-being, influencing their responses to stress and interactions. It extends beyond the mere absence of disorders, representing a state where individuals realize their potential and contribute positively to their communities. The global prevalence of mental health conditions, including anxiety and depression, presents significant challenges, with mental disorders contributing to substantial disability and premature mortality. Notably, those with severe mental conditions face life expectancies reduced by 10 to 20 years and increased risks of suicide and human rights violations. The COVID-19 pandemic has exacerbated these issues, highlighting the impact of societal inequalities and changes in work and lifestyle. In the Malaysian context, the trend of mental health issues has shown a worrying increase. Reports from the Ministry of Health and related agencies indicate a significant rise in cases of depression, anxiety, and suicidal ideation, especially among youth and young adults. The 2019 National Health and Morbidity Survey (NHMS) found that one in three Malaysian adults suffered from mental health issues, a statistic that is likely to have worsened post-pandemic. This surge has prompted growing concern over the adequacy of mental health support systems and the urgent need for integrated intervention strategies. The objective of this paper is to explore the intersection between the Kubler-Ross grief model and Surah Maryam from the Quran, analysing how these frameworks can inform mental health coping mechanisms and resilience. The Kubler-Ross model, with its stages of denial, anger, bargaining, depression, and acceptance, offers a psychological perspective on grief and terminal illness. In contrast, Surah Maryam presents a spiritual approach to mental health, emphasizing faith and reliance on Allah during trials. Through a qualitative analysis, this study contrasts these models, illustrating how Maryam's experience reflects a profound spiritual resilience that complements, and in some aspects transcends, the Kubler-Ross stages. By integrating these perspectives, the paper underscores the importance of incorporating both psychological and spiritual dimensions in understanding and addressing mental health challenges. The findings advocate for a holistic approach that incorporates spiritual beliefs and practices alongside conventional psychological frameworks to enhance mental well-being and resilience in the face of adversity.